2022
DOI: 10.1007/s11325-022-02563-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal application of soft-palate webbing flap pharyngoplasty combined with nasal surgery for surgical treatment of primary snoring and obstructive sleep apnea

Abstract: Background Excessive collapse of the soft palate and lateral pharyngeal wall narrowing are established causes of loud snoring and sleep apnea in subjects with obstructive sleep apnea (OSA). Therefore, delicate surgical techniques are needed to reshape the soft palate and create sufficient tension in the lateral pharyngeal wall. This study aimed to determine the therapeutic outcome and favorable indications of soft-palate webbing flap pharyngoplasty in subjects with OSA and primary snoring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Subgroup analysis revealed that OSA patients with mild/moderate disease severity (AHI < 30) had greater improvement in AHI, snoring score, ESS, REM% and LSAT than those with severe OSA, but the generally high heterogeneity with wide and overlapped CI of the both groups potentially indicated less statistical significance. On the other hand, the success rate was substantially higher in the mild/moderate OSA group than in the severe OSA group (mild/moderate vs. severe = 46% vs. 18%), which may imply that mild disease is easier to be corrected than severe disease, and is consistent with the concept promoted by the previous literature 27,28 . However, the results of subgroup analysis according to BMI were instead not consistent.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Subgroup analysis revealed that OSA patients with mild/moderate disease severity (AHI < 30) had greater improvement in AHI, snoring score, ESS, REM% and LSAT than those with severe OSA, but the generally high heterogeneity with wide and overlapped CI of the both groups potentially indicated less statistical significance. On the other hand, the success rate was substantially higher in the mild/moderate OSA group than in the severe OSA group (mild/moderate vs. severe = 46% vs. 18%), which may imply that mild disease is easier to be corrected than severe disease, and is consistent with the concept promoted by the previous literature 27,28 . However, the results of subgroup analysis according to BMI were instead not consistent.…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, the success rate was substantially higher in the mild/moderate OSA group than in the severe OSA group (mild/moderate vs. severe = 46% vs. 18%), which may imply that mild disease is easier to be corrected than severe disease, and is consistent with the concept promoted by the previous literature. 27,28 However, the results of subgroup analysis according to BMI were instead not consistent. The patients with BMI less than 27.5 had higher improvements in subjective outcomes including snoring VAS score and ESS, but the AHI improvement was higher in patients with BMI ≥ 27.5.…”
Section: Subgroup Analysesmentioning
confidence: 91%
“…In particular, the surgical outcome of SPWFPP was not successful and AHI score was aggravated in OSA patients with lateral pharyngeal wall collapse combined with epiglottis narrowing. SPWFPP provides a favorable improvement of sleep parameters in mild OSA patients or patients with primary snoring who had lateral bulk around the posterior pillar and circumferential narrowing at the retropalatal level in our previous study 10 . However, the present study showed that SPWFPP can be applied to OSA patients in whom lateral pharyngeal wall collapse is characteristic, especially in severe OSA patients.…”
Section: Discussionmentioning
confidence: 72%
“…In our previous data, we recommended SPWFPP to mild, moderate, and severe OSA patients with more than 50% narrowing in their lateral pharyngeal wall and tonsil enlargement, and we expected greater tension required to improve lateral pharyngeal wall collapse 10 . We found that SPWFPP yielded a 42.4% success rate and a 71.2% response rate in OSA patients with lateral pharyngeal wall collapse 10 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation